Management Culture Metaphysics: Chaos, Order, Harmony - Kovalenko, Yelena (Socio-Cultural Management Journal, 2021)
Introduction. Modern science, based on the abstract-logical method of cognition, is not able to comprehend the deep meaning of management culture in the organization processes of nature and society. A manager who uses a purely scientific approach will see only a part of the management object and not all its integrity and completeness. Purpose and methods. The purpose of the article is a metaphysical analysis of chaos, order, and harmony as fundamental concepts of general management culture, which will create a reliable tool for penetrating the depths of things and give not secondary interpretations, but to understand the essence of management culture yesterday, today and in the future. The methodological basis of the study is the metaphysical and dialectical principles of cognition, systemic and culturological approaches to the study of organizational phenomena and processes, as well as the fundamental provisions of the theory and history of culture. Results. The main approaches to the representation of chaos, order, and harmony in the mythopoetic picture of the world are considered. The most significant features of understanding chaos, order, and harmony in the philosophy of culture of the East are determined. The specifics of chaos, order, and harmony reflection in the philosophy of Western culture are revealed. A metaphysical synthesis of philosophical and scientific approaches to understanding chaos, order, and harmony in the context of management culture is carried out, and its deep essence is revealed. Conclusions. For the first time, a metaphysical analysis of chaos, order, and harmony in the organizational and cultural aspect was conducted, which allowed to penetrate the environment of transcendent management culture and to comprehend its deep meaning. The significance of the study is manifested in the addition of science to new theoretical provisions on the management culture metaphysics, as well as the possibility of using them in the training process of organizations’ managers.